(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
An experiment was conducted to study the effect of Citrulluscolocynthis seeds on the performance of broiler chickens, using dietscontaining four levels of C. colocynthis seed powder (0%, 2%, 4% and6%). Three hundred sixty males one day of age chicks (Ross strain) wererandomly allotted to four treatments with three replicates. All groups werefed ad libitum from one day to 49 days of age. Data were analyzedaccording to the completely randomized design, and Duncan’s multiplerange test was used for means comparison. Live body weight, carcassweight and dressing percentages significantly (P≤0.05) increased as thedietary level of C. colocynthis seeds increased. Feed intake, feedconversion ratio and abdominal fat pad weight significantly (P≤0.05)decreased as the dietary level of seed supplementation increased. Thegroup fed on 6% had significantly (P ≤ 0.05) the heaviest gastrointestinalweights (empty intestine, empty gizzard) and heart and liver weights.Therefore, C. colocynthis seeds can be added to broiler feeds up to 6%without adverse effects.